Penambahan konsentrat protein daun Wori (Ormocarpum cochinchinense) dalam pakan buatan untuk meningkatkan pertumbuhan dan sintasan hidup ikan Nila salin (Oreochromis niloctius): The Additon of Wori (Ormocarpum cochinchinense) Leaves Concentrate Protein in Artificial Feed on the Growth and Survival of Saline Tilapia - Mose, Numisye Iske; Saselah , Jetti (Universitas Sam Ratulangi, 2024)
Ormocarpum cochinchinense leaves protein concentrate (KPDW) is a product resulting from making protein concentrate using the coagulation method on wori leaves. The addition of KPDW in artificial feed is expected to increase the nutrition of the feed so that it can increase the growth of saline tilapia in ponds. The aim of this research was to analyze the effect of adding KPDW to artificial feed on the growth and survival rate of saline tilapia. Saline tilapia was reared in the West Petta Village Pond, Petta District, Sangihe Islands Regency. This research used a completely randomized design method consisting of 4 treatments, each with 3 replications, namely control, the addition of 1%, 2%, and 3% KPDW. The results obtained from this research were that the addition of 1% KPDW to artificial feed provided better absolute weight and absolute length of saline tilapia compared to adding KPDW at other doses, meanwhile, the survival value of saline tilapia in all treatments was 100%. In conclusion, the addition of KPDW to artificial feed had no significant effect on the growth and survival of saline tilapia. Keywords: aquaculture, protein source, alternative feed